Long‐term magnesium supplementation improves glucocorticoid metabolism: A post‐hoc analysis of an intervention trial. (26th October 2020) - Schutten, Joëlle C.; Joris, Peter J.; Minović, Isidor; Post, Adrian; van Beek, André P.; de Borst, Martin H.; Mensink, Ronald P.; Bakker, Stephan J. L.
Abstract: Objective: Increasing magnesium intake might reduce the risk of cardiovascular disease (CVD). Whether potential effects on cortisol contribute to these beneficial effects on cardiovascular health remains unclear. We therefore studied effects of long‐term oral magnesium supplementation on glucocorticoid metabolism, specifically on the excretion of urinary cortisol, cortisone and their metabolites, as well as on the ratios reflecting enzymatic activity of 11β‐hydroxysteroid dehydrogenases (11β‐HSDs) and A‐ring reductases. Design: A post‐hoc analysis of a randomized trial with allocation to a magnesium supplement (350 mg/day) or a placebo for 24‐week. Patients: Forty‐nine overweight men and women, aged between 45 and 70 years. Measurements: Cortisol, cortisone and their metabolites (tetrahydrocortisol [THF], allo‐tetrahydrocortisol [allo‐THF] and tetrahydrocortisone [THE]) were measured in 24‐h urine samples. Enzymatic activities of 11β‐HSD overall and of 11β‐HSD type 2 were estimated as the urinary (THF + allo‐THF [THFs])/THE and cortisol/cortisone ratios, respectively. A‐ring reductase activity was assessed by ratios of THF/allo‐THF, allo‐THF/cortisol, THF/cortisol and THE/cortisone. Results: After 24‐week, urinary cortisol excretion was decreased in the magnesium group as compared with the placebo group (−32 nmol/24‐h, 95% CI: −59; −5 nmol/24‐h, p  = .021). Ratios of THFs/THE and cortisol/cortisone were decreased following magnesium supplementation by 0.09 (95% CI: 0.02; 0.17, p  = .018) and 0.10 (95% CI: 0.03; 0.17, p  = .005), respectively. No effects were observed on A‐ring reductase activity. Conclusions: We observed a beneficial effect of magnesium supplementation towards a lower 24‐h urinary cortisol excretion together with an increased activity of 11β‐HSD type 2. Our findings may provide another potential mechanism by which increased magnesium intake lowers CVD risk (ClinicalTrials.gov identifier: NCT02235805).